Iran - Simmons, Walter (Walter G.) (Minneapolis, MN : Bellwether Media, 2011)
"Developed by literacy experts for students in grades three through seven, this book introduces young readers to the geography and culture of Iran"--Provided by publisher.
Where is Iran? -- The land -- Bam -- Wildlife -- The people -- Daily life -- Going to school -- Working -- Playing -- Food -- Holidays -- Life in Tehran -- Fast facts -- National flag -- Glossary.
Includes bibliographical references and index.
Keywords: Iran -- Juvenile literature